Magnetic nano-sized solid acid catalyst bearing sulfonic acid groups for biodiesel synthesis and oxidation of sulfides - Durgesh Singh; Kamini Singh; Yashwantsinh Jadeja; Soumya V. Menon; Priyanka Singh; Safaa Mohammed Ibrahim; Manmeet Singh; Munther Kadhim Abosaoda; Salwa Bader Al Reshaidan; Mohammed A. El-Meligy (Scientific Reports)
Abstract In this study, the AlFe2O4@n-Pr@Et-SO3H heterogeneous catalyst was successfully synthesized and utilized to produce biodiesel from oleic acid through an esterification process and to oxidize sulfides. To examine the physicochemical characteristics of the AlFe2O4@n-Pr@Et-SO3H nanomaterial, a variety of advanced techniques were employed, including Fourier Transform infrared spectroscopy (FT-IR), Field emission scanning electron microscopy (FE-SEM), Energy dispersive X-ray spectroscopy (EDX), Vibrating sample magnetometer (VSM), Elemental Mapping, Transmission electron microscopy (TEM), Inductively coupled plasma (ICP), and X-ray diffraction (XRD). The AlFe2O4@n-Pr@Et-SO3H materials demonstrated excellent performance in both the esterification of oleic acid and the oxidation of sulfides. Moreover, the catalyst can be easily recovered and reused multiple times without a significant reduction in its effectiveness.